Nutritional evaluation of gluten-free foods available in the Portuguese market - Capelas, R. (2020)
Introduction: Management of coeliac disease requires the removal of gluten from the diet. Over the last years, gluten-free foods in the market has expanded rapidly, not only for an increase in the number of coeliac disease patients, but also due to the consumer’s perception that these foods are a healthier option. Nevertheless, the nutritional quality of processed gluten-free products is a common concern. This work aims to clarify the nutritional composition of processed gluten-free products, considering the dietary recommendations and needs. Methods: During 2019, gluten-free foods available in the major Portuguese supermarkets through online retailer websites were evaluated. For each gluten-free food, information concerning ingredients, cost and nutritional values was registered in an Excel® database. Gluten-free foods were grouped in: (i) Bread, pasta, cereals and flours; (ii) Cookies and biscuits; and (iii) Pastry products. The accuracy of the nutritional declaration of the selected foods was assessed considering Regulation (EU) n.º 1169/2011. The nutritional quality of these foods was evaluated taking into account the recommendations of the Portuguese Integrated Strategy for the Promotion of Healthy Eating (EIPAS). Results: A total of 294 gluten-free foods were included in the database: bread, pasta, cereals and flours (n=147), biscuits and cookies (n=107) and pastry products (n=40). According to Regulation (EU) n.º 1169/2011, it is mandatory to declare the energy value and the amounts of fat, saturated fatty acids, carbohydrates and sugars, protein and salt. In this study, 26 out of 294 gluten-free foods have missing data concerning one or more of the mandatory nutrients. According to EIPAS, it is intended to achieve a salt content lower than 0.3 g/100 g. Our results showed that only 73 of the selected gluten-free comply with the desired salt content fixed by EIPAS. Discussion: Despite improvements in the market of gluten-free foods, these type of foods are still more expensive than similar ones with gluten. Concerning the accuracy of the labelling, some minor discrepancies were found, indicating efforts to accomplish the declaration of mandatory nutrients. The nutritional composition of these foods suggest that they still have high amounts of fat, especially saturated fat, and the levels of salt are far away from the desired goals. Therefore, the reformulation of these foods, which is a desired goal by the national and international organizations, to offer healthier options to consumers, should be also targeted for gluten-free products.